2005
DOI: 10.1007/s10641-004-2864-y
|View full text |Cite
|
Sign up to set email alerts
|

Movement of walleye in an impounded reach of the Au Sable River, Michigan, USA

Abstract: SynopsisWe estimated long-range spawning and foraging movements of walleye and observed their use of river and reservoir habitats between two large hydroelectric dams on the Au Sable River, Michigan. We used radiotelemetry to monitor seasonal and daily movements of 11 large walleye. Walleye ranged throughout the entire reach between the two dams. Eight of the 11 fish used both river and reservoir locations. Walleye migrated upriver in April or May and presumably spawned near the dam tailwaters. After spawning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…Thus groundwater fed tributaries are important in sustaining the cold-and cool-water fish species (Clapp et al, 1990;Wiley et al, 1997;Brazner et al, 2005;Creque et al, 2005), which are common in much of the river system. Nonetheless, there is concern that a number of important fishes may become susceptible to thermal stresses (O'Neal, 1997;DePhilip et al, 2005;Larson et al, 2013) resulting from land use changes (e.g., urban sprawl) (Pijanowski et al, 2006(Pijanowski et al, , 2007, climate change , and hydropower production (Horne et al, 2004).…”
Section: Study Areamentioning
confidence: 99%
“…Thus groundwater fed tributaries are important in sustaining the cold-and cool-water fish species (Clapp et al, 1990;Wiley et al, 1997;Brazner et al, 2005;Creque et al, 2005), which are common in much of the river system. Nonetheless, there is concern that a number of important fishes may become susceptible to thermal stresses (O'Neal, 1997;DePhilip et al, 2005;Larson et al, 2013) resulting from land use changes (e.g., urban sprawl) (Pijanowski et al, 2006(Pijanowski et al, , 2007, climate change , and hydropower production (Horne et al, 2004).…”
Section: Study Areamentioning
confidence: 99%
“…Severe effects of entrainment include direct mortality and injury resulting from shear stress, barotrauma and contact with turbines and water release structures (Čada, ). Regardless of the effects of entrainment, these impacts are often magnified as discharge increases and more fish are entrained (DePhilip et al., ; Fincel et al., ; Perry et al., ; Spoelstra et al., ). From a fisheries management perspective, the efficacy of otolith chemistry for evaluating walleye environmental history indicates that managers can use this technique as a predictive tool to forecast movement and entrainment in baseline and flood conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Entrainment may also cause changes in fish population dynamics (e.g. recruitment, growth, mortality) or elicit novel fish community interactions, including predation and competition (DePhilip et al, 2005;Perry et al, 2015). Moreover, genetic integrity may decline if entrained fish interbreed with individuals in recipient locations (Spoelstra et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mean of the final gamma distribution describing migration rate was 10.7 km·day −1 , with a standard deviation of 10.1 km·day −1 , capturing the great amount of variability in the measurement of migration rate observed with each method. Past studies have measured walleye migration rates in other systems and reported values have ranged from approximately 4 km·day −1 (Palmer et al 2005) to 10 km·day −1 (Paragamian 1989;DePhilip et al 2005), which are contained within the modeled migration rate distribution used in this study.…”
Section: Estimating Migration Ratementioning
confidence: 92%